Exploring entrepreneurial intentions in Latin American university students - Contreras Torres, Francoise (2017)
The aim of this study was to determine if entrepreneurial intention, based on Ajzen’s model of planned behavior (1991), can be predicted by risk propensity, internal locus of control and leadership skills. Six standardized and reliable instruments were applied to 1493 undergraduate university business students in Latin American countries, selected through non-random quota sampling in accordance with their formation level in each of the five participating universities. Using structural equation techniques, the research model was validated and intention estimated and analyzed in relation to a set of socio-demographic variables. According to the results, entrepreneurial intention can be significantly predicted by the psychological variables under consideration and, contrary to what has been reported in other research, no gender differences were found in the intention of entrepreneurship. These findings are discussed.